Four visions of history: The ideal of liberty in Ecuadorian women's journalism - Sánchez Carrión, Gabriela; Punín Larrea, María Isabel (Historia y Comunicación Social, 2021)
It is a documentary and bibliographic investigation, analyzes and rescues the contribution to journalism and gender equality in Ecuador, through four emblematic women in two different times: Zoila Ugarte de Landívar (1868/1969) and Nela Martínez Espinosa (1912 / 2004); Mariana Neira López (1950) and Tania Tinoco Márquez (1963). The main method is the analysis of discourse, taking into account four research variables: feminism, journalism, politics and society. It is a comparative and semantic study, to identify analogies and singularities in the behavior and social influence of the women mentioned, whose lives were marked by a liberation of an intellectual nature.
Keywords: woman; liberty; liberalism; journalism; Ecuador